GERAKAN JAMAAH DAN DAKWAH JAMAAH MUHAMMADIYAH: REKONTEKSTUALISASI TARJIH DALAM PENGUATAN KEBERAGAMAAN MASYARAKAT LOKAL - Imam Sholihin; Bagus Jamroji; Lina Alfiah; Suwadi Pranoto; Ziaul Rahman Baihaqi (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study examines the role of gerakan jamaah and dakwah jamaah implemented by Muhammadiyah as a medium for recontextualizing tarjih thought in strengthening local religious life. Employing a qualitative descriptive-analytical approach, the research draws on data collected through observation, in-depth interviews, and document analysis involving Muhammadiyah activists, preachers, and community members. The findings reveal that community-based da‘wah enables the contextual internalization of normative Islamic values through participatory and dialogical engagement, fostering both individual piety and social religiosity. Furthermore, the study demonstrates that the integration of tarjih methodology with dakwah jamaah facilitates a dynamic interaction between religious normativity and local socio-cultural realities without altering the substantive principles of Islamic teachings. Despite facing challenges such as diverse religious traditions and limited human resources, dakwah jamaah proves effective in promoting moderate, inclusive, and progressive religiosity. This research contributes to the discourse on Al-Islam and Muhammadiyah studies by highlighting the strategic significance of community-based da‘wah in addressing contemporary religious challenges at the local level.